header bg

Question:

Solve for x:
5(4x + 3) – 4(2x + 1) = 47

A x = 3
Explaination

Step 1: Apply the distributive law
The first step is to expand the terms 5(4x + 3) and 4(2x + 1) by distribution so 5(4x + 3) – 4(2x + 1) = 47 becomes
20x + 15 – 8x – 4 = 47.
Step 2: Combine like terms
We can then collect like terms in 20x + 15 – 8x – 4 = 47.
12x + 11 = 47
Step 3: Subtract 11 on both sides
We then have to subtract 11 on both sides to isolate the term with x.
12x + 11 – 11 = 47 – 11
12x = 36
Step 4: Divide by 12 on both sides
We then divide both sides of the equation by 12 to isolate x.
(12x)/12 = 36/12
1x = 3
We can drop the 1 on the left-hand side to x = 3.
x = 3 is the solution of the equation.